Influence of crosslinking on the drug release of PLLA/gelatin nonwovens - Wulf Katharina; Grabow Niels; Illner Sabine (Current Directions in Biomedical Engineering, 2022)
Electrospun fibers based on synthetic and natural polymers represent a promising approach in order to mimic the mechanical stability and the required cell-polymer interaction of the natural extracellular matrix (ECM), . In this biomedical context, the biodegradable medical grade poly-llactide (PLLA) and the natural gelatin are already well established. However, to obtain a stabilized structured PLLA/gelatin blend, crosslinking of gelatin is required. In this study, the influence of the post processed crosslinking via Glutaraldehyde (GTA) vapor and GTA solution on the morphological and physicochemical properties of the blend, as well as on the in vitrorelease of previously incorporated dexamethasone (DMS), was investigated. The addition of gelatin decreased the fiber diameter and increased the surface hydrophilicity, which is furthermore unaffected by the crosslinking process. The in vitrorelease of DMS was decisively changed by both, the addition of gelatin and the subsequent crosslinking processes. For all modified samples, a very rapid burst release of DMS was detected within the first 24 h, which is crucial for biomedical applications such as tumor therapy.